Is testosterone replacement therapy in males with hypogonadism cost-effective? An analysis in Sweden - Arver, Stefan; Luong, Ba; Fraschke, Anina; Ghatnekar, Ola; Stanisic, Sanja; Gultyev, Dmitry; Müller, Elvira (Journal of sexual medicine, 2014)
Testosterone replacement therapy (TRT) has been recommended for the treatment of primary and secondary hypogonadism. However, long-term implications of TRT have not been investigated extensively. The aim of this analysis was to evaluate health outcomes and costs associated with life-long TRT in patients suffering from Klinefelter syndrome and late-onset hypogonadism (LOH). A Markov model was developed to assess cost-effectiveness of testosterone undecanoate (TU) depot injection treatment compared with no treatment. Health outcomes and associated costs were modeled in monthly cycles per patient individually along a lifetime horizon. Modeled health outcomes included development of type 2 diabetes, depression, cardiovascular and cerebrovascular complications, and fractures. Analysis was performed for the Swedish health-care setting from health-care payer's and societal perspective. One-way sensitivity analyses evaluated the robustness of results. The main outcome measures were quality-adjusted life-years (QALYs) and total cost in TU depot injection treatment and no treatment cohorts. In addition, outcomes were also expressed as incremental cost per QALY gained for TU depot injection therapy compared with no treatment (incremental cost-effectiveness ratio [ICER]). TU depot injection compared to no-treatment yielded a gain of 1.67 QALYs at an incremental cost of 28,176 EUR (37,192 USD) in the Klinefelter population. The ICER was 16,884 EUR (22,287 USD) per QALY gained. Outcomes in LOH population estimated benefits of TRT at 19,719 EUR (26,029 USD) per QALY gained. Results showed to be considerably robust when tested in sensitivity analyses. Variation of relative risk to develop type 2 diabetes had the highest impact on long-term outcomes in both patient groups. This analysis suggests that lifelong TU depot injection therapy of patients with hypogonadism is a cost-effective treatment in Sweden. Hence, it can support clinicians in decision making when considering appropriate treatment strategies for patients with testosterone deficiency.